ОСОБЛИВОСТІ АТЕСТАЦІЇ ЗДОБУВАЧІВ ОСВІТИ У ЗАКЛАДАХ ФАХОВОЇ ПЕРЕДВИЩОЇ ОСВІТИ У ПЕРІОДИ ДИСТАНЦІЙНОГО НАВЧАННЯ (Innovative professional education, 2022)
In the conditions of distance learning, the use of the Google platform has been introduced at the college for conducting the "Comprehensive Qualification Examination" under the educational and professional program "Accounting". Taking into account the large amount of theoretical knowledge, practical skills, as well as modern special conditions of study, the examination is divided into three stages. This format of conducting a comprehensive qualification exam allows to more objectively determine the level of training of a specialist.
Keywords: attestation of applicants, institutions of vocational pre-higher education, comprehensive qualification exam, stages of the exam, distance learning